Pemex

Solo disponible en BuenasTareas
  • Páginas : 2 (372 palabras )
  • Descarga(s) : 0
  • Publicado : 18 de noviembre de 2011
Leer documento completo
Vista previa del texto
Dᵪ(uᶯ) = nuᶯ̵¹Dᵪu Dᵪ(uᶯ) = nuᶯ̵¹Dᵪu Dᵪ(u + v) = Dᵪu + Dᵪv |

Dᵪ(u + v) = Dᵪ(u v) = Dᵪ(u v) = Dᵪu +Dᵪv u Dᵪv + v Dᵪu u Dᵪv + v Dᵪu |
Dᵪ(uv) = Dᵪ(uv) = Dᵪ(eᶸ) = eᶸ DᵪuvDᵪu- uDᵪv v² vDᵪu- uDᵪv v² |
Dᵪ(eᶸ) = eᶸ DᵪuDᵪ(aᶸ) = aᶸ In a Dᵪu Dᵪ(aᶸ) = aᶸ In a Dᵪu |
Dᵪ(In u) = 1uDᵪu Dᵪ(In u) = 1uDᵪu Dᵪ(sen u) = cos u Dᵪu |
Dᵪ(sen u) = cos u Dᵪu Dᵪ(cos u) = Dᵪ(cos u)=-sen u Dᵪu -sen u Dᵪu|
Dᵪ(tan u) Dᵪu Dᵪ(tan u) = Dᵪ(cot u) = = sec2 u sec2 u Dᵪu -csc2 u Dᵪu |Dᵪ(cot u) = Dᵪ(sec u) = Dᵪ(sec u) = -csc2 u Dᵪu sec u tan u Dᵪu sec u tan u Dᵪu |
Dᵪ(csc u) = Dᵪ(csc u)Dᵪ(sen-1u) =-csc u cot u Dᵪu = -csc u cot u Dᵪu 11-u2 Dᵪ u |
Dᵪ(sen-1u) = Dᵪ(cos-1u) = Dᵪ(cos-1u) = 11-u2 Dᵪ u -11-u2 Dᵪu-11-u2 Dᵪu |
Dᵪ(tan-1u) = Dᵪ(tan-1u) = Dᵪ(cot-1u) = 11+ u2 Dᵪu 11+ u2 Dᵪu -11+ u2 Dᵪu |
Dᵪ(cot-1u) = Dᵪ(sec-1u) = Dᵪ(sec-1u)= -11+ u2 Dᵪu 1uu2- 1 Dᵪu 1uu2- 1 Dᵪu |
Dᵪ(csc-1u) = Dᵪ(csc-1u) = Dᵪ(senh u) = -1uu2- 1 Dᵪu -1uu2- 1 Dᵪu cosh u Dᵪu|
Dᵪ(senh u) = Dᵪ(cosh u) = Dᵪ(cosh u) =cosh u Dᵪu senh u Dᵪu senh u Dᵪu |
Dᵪ(tanh u) = Dᵪ(tanh u) = Dᵪ(coth u) =...
tracking img